Prophylactic use of ketamine reduces postpartum depression in Chinese women undergoing cesarean section✰. (September 2019) - Ma, Jia-Hui; Wang, Sai-Ying; Yu, He-Ya; Li, Dan-Yang; Luo, Shi-Chao; Zheng, Shan-Shan; Wan, Li-Fei; Duan, Kai-Ming
Highlights: l Ketamine functioned as a prophylactic agent against postpartum depression. l Ketamine relieved suicidal ideation in women with postpartum depression. l The antidepressant efficacy of ketamine was more obvious in some subgroups. (e.g., women with antenatal depressive symptom and antenatal suicidal ideation). Abstract: This study aimed to explore the effect of prophylactic ketamine administration on postpartum depression in Chinese woman undergoing cesarean section. This randomized controlled study included 654 Chinese women undergoing cesarean section. At 10 min after child birth, patients in the ketamine group were given 0.5 mg/kg ketamine, whereas patients in the control group received standard postpartum care. At the end of operation, all patients were armed with a patient-controlled intravenous analgesia device. The primary outcome was the prevalence of postpartum depression (PPD), as assessed by the Edinburgh Postnatal Depression Scale (EPDS), and the secondary outcomes included the safety assessment and the Numerical Rating Scale (NRS) of postoperative pain. The prevalence of postpartum blues and postpartum depression were significantly lower in the ketamine group than in the control group. Logistic analysis showed that ketamine administration protected against postpartum depression, and PPD-associated risk factors included stress during pregnancy, antenatal depressive symptom and antenatal suicidal ideation. In addition, the antidepressive effect of prophylactic ketamine was stronger in mothers with a history of moderate stress during pregnancy, antenatal depressive symptom and antenatal suicidal ideation. Our findings suggest that ketamine functions as a prophylactic agent against PPD.